Evaluation of the Effectiveness of Disaster Mitigation Based Spatial Planning Policies in West Sumatra: Literature Review - Azzahra, Nabila; Jelibseda, Jelibseda; Syah, Nurhasan; Heldi, Heldi; Catri, Indra (Postgraduate School, Universitas Negeri Padang, 2024)
This study aims to evaluate the effectiveness of disaster mitigation-based spatial planning policies in West Sumatra. The research employs a qualitative approach with a case study method to conduct an in-depth analysis of policy implementation and its practical outcomes. Data was collected from various sources, including policy documents, reports from the National Disaster Management Agency (BNPB), and scientific literature. The results indicate that while the policies have shown some positive impacts, such as reducing disaster risks and improving infrastructure resilience, their implementation remains suboptimal due to key challenges. These include weak coordination among stakeholders, limited resources, and inadequate public participation. For instance, spatial planning regulations, such as the Regional Spatial Plan (RTRW), often lack integration, leading to inconsistent policy enforcement. Moreover, resource constraints, both financial and human, hinder the execution of mitigation programs. The community's limited awareness and involvement further complicate efforts, as policies often fail to address local needs effectively. To enhance policy effectiveness, this study recommends strengthening inter-agency coordination, enforcing strict compliance measures, and fostering community participation through inclusive planning approaches. Evaluating and refining existing policies is crucial for West Sumatra to achieve disaster resilience and sustainable development.